Lithium secondary battery

By employing an adsorbing agent like activated carbon within the lithium secondary battery to adsorb sulfur-containing positive electrode active materials, the battery's capacity loss and structural deformation issues due to high temperature exposure are mitigated.

JP7666008B2Active Publication Date: 2025-04-22NISSAN MOTOR CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021024173
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-18
Publication Date
2025-04-22
Estimated Expiration
2041-02-18

AI Technical Summary

Technical Problem

Lithium secondary batteries using sulfur-containing positive electrode active materials face issues with deformation and capacity loss due to melting or sublimation at high temperatures, which is not effectively addressed by existing frame structures.

Method used

Incorporating an adsorbing agent, such as activated carbon, within the battery exterior material to adsorb the sulfur-containing positive electrode active material, thereby minimizing deformation and preventing local battery reactions.

Benefits of technology

The use of an adsorbing agent effectively suppresses the decrease in battery capacity caused by high temperature-induced melting or sublimation of sulfur-containing materials, while also minimizing structural deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666008000002
    Figure 0007666008000002
  • Figure 0007666008000003
    Figure 0007666008000003
  • Figure 0007666008000004
    Figure 0007666008000004
Patent Text Reader

Abstract

To provide means capable of suppressing decrease in battery capacity due to melting and sublimation of a positive electrode active material when a battery is exposed to high temperatures while minimizing deformation of a structure of a power generation element in a lithium secondary battery using a positive electrode active material containing sulfur.SOLUTION: In a lithium secondary battery using a positive electrode active material containing sulfur, an adsorbent capable of adsorbing a positive electrode active material is arranged in an internal space of a battery exterior material in which a power generating element is enclosed.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium secondary battery. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and there has been active development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these into practical use.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.

[0004] Currently, lithium secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and these liquid-based lithium secondary batteries require stricter safety measures against leakage, short circuits, overcharging, etc. than other batteries.

[0005] In recent years, research and development of all-solid-state lithium secondary batteries using oxide-based or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material that is mainly composed of an ion conductor capable of ion conduction in a solid state. Therefore, in principle, all-solid-state lithium secondary batteries do not have various problems caused by flammable organic electrolytes, as in conventional liquid-based lithium secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery. For example, elemental sulfur (S8) has an extremely large theoretical capacity of about 1670 mAh / g, and has the advantages of being low cost and abundant in resources.

[0006] Incidentally, Patent Document 1 discloses a technique for preventing deformation of a laminate caused by pressure applied during molding and bonding of the electrodes and the solid electrolyte layer by disposing a frame-shaped heat-resistant insulating member on the outer periphery of a laminate of a positive electrode active material layer / solid electrolyte layer / negative electrode active material layer when manufacturing a solid sheet-type battery. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2010 / 131321 Brochure Summary of the Invention [Problem to be solved by the invention]

[0008] Generally, a cathode active material containing sulfur such as elemental sulfur has a lower melting point or sublimation temperature than other cathode active materials. Therefore, when a lithium secondary battery using such a cathode active material is exposed to high temperatures, the cathode active material melts or sublimes. The present inventors have found that when the sulfur-containing cathode active material melts or sublimes under such high temperature conditions and reaches the anode active material layer, a local battery reaction proceeds and the capacity of the battery decreases. In order to solve this problem, the inventors have considered arranging a frame structure as disclosed in Patent Document 1 on the outer periphery of the active material layer. However, when such a frame structure is arranged, the molten or sublimated active material is held inside the space partitioned by the frame structure. Therefore, it has been found that the pressure inside the frame structure increases, and the active material layer deforms and expands, which may cause deformation of the cell.

[0009] Therefore, an object of the present invention is to provide a means for suppressing a decrease in battery capacity caused by melting or sublimation of the positive electrode active material when the battery is exposed to high temperatures, while minimizing deformation of the structure of the power generating element in a lithium secondary battery using a positive electrode active material containing sulfur. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that the above problems can be solved by disposing an adsorbent capable of adsorbing a positive electrode active material in an internal space of a battery exterior material in which a power generating element is enclosed, in a lithium secondary battery using a positive electrode active material containing sulfur, and have thus completed the present invention.

[0011] A lithium secondary battery according to one embodiment of the present invention has a configuration in which a power generating element including a positive electrode including a positive electrode active material layer containing a positive electrode active material containing sulfur, a negative electrode including a negative electrode active material layer containing a negative electrode active material containing lithium, and a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer are enclosed inside a battery exterior material, and is characterized in that an adsorbent capable of adsorbing the positive electrode active material is disposed in the internal space of the battery exterior material in which the power generating element is enclosed. Effect of the Invention

[0012] According to the present invention, in a lithium secondary battery using a positive electrode active material containing sulfur, it is possible to minimize deformation of the structure of the power generating element while suppressing a decrease in battery capacity caused by melting or sublimation of the positive electrode active material when the battery is exposed to high temperatures. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a perspective view showing the appearance of a stacked battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view taken along line 2-2 shown in FIG. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of a unit cell layer that constitutes the power generating element of the stacked battery shown in FIGS. [Figure 4] FIG. 4 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Diagram 5] FIG. 5 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Figure 6] FIG. 6 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Figure 7] FIG. 7 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Figure 8] FIG. 8 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Figure 9] FIG. 9 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. [Figure 10] FIG. 10 is a cross-sectional view showing a modified example of the laminated battery according to the embodiment shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] One embodiment of the present invention is a lithium secondary battery in which a power generating element having a positive electrode including a positive electrode active material layer containing a positive electrode active material containing sulfur, a negative electrode including a negative electrode active material layer containing a negative electrode active material containing lithium, and a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer is enclosed inside a battery exterior material, and an adsorbent capable of adsorbing the positive electrode active material is disposed in an internal space of the battery exterior material in which the power generating element is enclosed.

[0015] Hereinafter, the above-mentioned embodiment of the present invention will be described with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to only the following embodiment. The dimensional ratios in the drawings are exaggerated for convenience of explanation and may differ from the actual ratios. Hereinafter, the present invention will be described using a non-bipolar (internal parallel connection type) flat laminated all-solid-state lithium secondary battery (hereinafter simply referred to as a "laminated battery"), which is one form of secondary battery, as an example. As described above, the solid electrolyte constituting the all-solid-state lithium secondary battery is a material mainly composed of an ion conductor capable of ion conduction in a solid. For this reason, the all-solid-state lithium secondary battery has the advantage that, in principle, various problems caused by flammable organic electrolytes do not occur, as in the conventional liquid-based lithium secondary batteries. In addition, in general, there is also the advantage that the output density and energy density of the battery can be significantly improved by using a high-potential, large-capacity positive electrode material and a large-capacity negative electrode material.

[0016] Fig. 1 is a perspective view showing the appearance of a stacked battery according to one embodiment of the present invention. Fig. 2 is a cross-sectional view taken along line 2-2 shown in Fig. 1. The stacked type allows the battery to be compact and have a high capacity.

[0017] 1, the stacked battery 10a has a flat rectangular shape, with a positive current collector 27 and a negative current collector 25 for extracting power extending from both sides. The power generating element 21 is wrapped in a battery exterior material (laminate film 29) of the stacked battery 10a, and the periphery is heat-sealed, with the power generating element 21 being sealed in a state in which the positive current collector 27 and the negative current collector 25 extend to the outside.

[0018] The all-solid-state battery according to the present embodiment is not limited to a laminated flat shape. A wound all-solid-state battery may be cylindrical, or may be a cylindrical shape modified to have a rectangular flat shape, and is not particularly limited. The cylindrical shape may be a laminate film or a conventional cylindrical can (metal can) as an exterior material, and is not particularly limited. Preferably, the power generating element is housed inside a laminate film containing aluminum. This form can achieve weight reduction.

[0019] There is also no particular limitation on the removal of the current collectors (27, 25) shown in Fig. 1. The positive current collector 27 and the negative current collector 25 may be pulled out from the same side, or the positive current collector 27 and the negative current collector 25 may each be divided into a plurality of pieces and removed from each side, and are not limited to what is shown in Fig. 1. In addition, in a wound type lithium ion battery, the terminals may be formed using, for example, a cylindrical can (metal can) instead of a tab.

[0020] 2, the stacked battery 10a of this embodiment has a structure in which a flat, generally rectangular power generating element 21, where charge and discharge reactions actually proceed, is sealed inside a laminate film 29, which is a battery exterior material. Here, the power generating element 21 has a configuration in which a positive electrode, a solid electrolyte layer 17, and a negative electrode are laminated. In this embodiment, the solid electrolyte layer 17 contains LPS (Li2S-P2S5), which is a type of sulfide solid electrolyte. The positive electrode has a structure in which positive electrode active material layers 15 containing a positive electrode active material (here, elemental sulfur (S)) are arranged on both sides of a positive electrode collector 11". The negative electrode has a structure in which negative electrode active material layers 13 containing a negative electrode active material (here, an In-Li alloy) are arranged on both sides of a negative electrode collector 11'. Specifically, the positive electrode, solid electrolyte layer, and negative electrode are stacked in this order such that one positive electrode active material layer 15 and an adjacent negative electrode active material layer 13 face each other with a solid electrolyte layer 17 interposed therebetween. As a result, the adjacent positive electrode, solid electrolyte layer, and negative electrode constitute one unit cell layer 19. Therefore, it can be said that the stacked battery 10a shown in FIG. 2 has a structure in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0021] Positive current collector 11" and negative current collector 11' are respectively attached with positive current collector (tab) 27 and negative current collector (tab) 25 that are electrically connected to the respective electrodes (positive and negative electrodes), and have a structure in which they are sandwiched between ends of laminate film 29, which is a battery exterior material, and are led out of laminate film 29. Positive current collector 27 and negative current collector 25 may be attached to positive current collector 11" and negative current collector 11' of each electrode by ultrasonic welding, resistance welding, or the like, via positive electrode leads and negative electrode leads (not shown) as necessary.

[0022] FIG. 3 is an enlarged cross-sectional view of a single cell layer 19 constituting the power generating element 21 of the stacked battery 10a shown in FIGS.

[0023] In this embodiment, as shown in FIG. 2 and FIG. 3, an activated carbon layer 23 as an adsorbent capable of adsorbing a positive electrode active material is disposed so as to cover the outer peripheral end of the positive electrode active material layer 15 and the positive electrode current collector 11″ (details of the adsorbent will be described later). Here, the activated carbon layer 23 as an adsorbent is continuously provided in the stacking direction from one solid electrolyte layer 17 located in the adjacent single cell layer 19 to the other solid electrolyte layer 17 over the entire periphery of the outer peripheral end of the positive electrode active material layer 15 and the positive electrode current collector 11″ (however, the positive electrode (Excluding the portion where current is taken out from current collector 11"). With this configuration, even if there is a risk that the sulfur-containing positive electrode active material melts or sublimes and leaks from the positive electrode active material layer when the battery is exposed to high temperatures, activated carbon layer 23 adsorbs the melted or sublimated positive electrode active material. This prevents the melted or sublimated positive electrode active material from migrating to the negative electrode active material layer and causing a local battery reaction. In this way, it is possible to prevent a decrease in battery capacity due to the progress of the local battery reaction as described above.

[0024] In the laminated battery 10a according to this embodiment, the arrangement of the activated carbon layer 23 as the adsorbent is not limited to the arrangement shown in FIG. 2 and FIG. 3. For example, in the modified example shown in FIG. 4, the outer periphery of the activated carbon layer 23 has a tapered shape. In the modified example shown in FIG. 5, the activated carbon layer 23 does not cover the entire outer periphery of the positive electrode active material layer 15, but is arranged on the surface of the solid electrolyte layer 17. In the modified example shown in FIG. 6, the activated carbon layer 23 is arranged so as to cover the outer periphery of the negative electrode active material layer 13 and the negative electrode current collector 11'. In this way, the adsorbent according to this embodiment is preferably arranged on the outer periphery of at least one positive electrode active material layer and / or at least one negative electrode active material layer. In this case, it is more preferable that the adsorbent is arranged on the surface of the solid electrolyte layer at the outer periphery of at least one positive electrode active material layer and / or at least one negative electrode active material layer. It is also preferable that the adsorbent is disposed on the surface of the active material layer at the outer peripheral end of at least one of the positive electrode active material layers and / or at least one of the negative electrode active material layers, which is not facing the counter electrode. With such a configuration, when the battery is exposed to high temperatures, it is possible to effectively prevent the positive electrode active material that has melted or sublimated from contacting the negative electrode active material layer 13 and causing a local battery reaction, which would otherwise cause a decrease in the battery capacity.

[0025] In another embodiment of the present invention, a protective part not containing an adsorbent is further disposed at the outer peripheral end of at least one positive electrode active material layer and / or at least one negative electrode active material layer (details of such a protective part will be described later). For example, in the embodiment shown in FIG. 7, a polyethylene terephthalate (PET) resin layer 24 is disposed as a protective part so as to cover the outer periphery of the activated carbon layer 23 shown in FIG. 3. By providing such a protective part, even if the adsorbent such as the activated carbon layer 23 is not able to adsorb the molten or sublimated positive electrode active material, it is possible to reliably prevent the molten or sublimated positive electrode active material from coming into contact with the negative electrode active material layer 13. There is no particular restriction on the arrangement of the protective part. For example, in the modified example shown in FIG. 8, a PET resin layer 24 having a tapered shape corresponding to the tapered shape of the activated carbon layer 23 shown in FIG. 4 is disposed so as to cover the outer periphery of the activated carbon layer 23. In the modified example shown in FIG. 9, a PET resin layer 24 is disposed on the exposed surface of the activated carbon layer 23 shown in FIG. 5. In the modification shown in FIG. 10, a PET resin layer 24 is disposed as a protective part on the outer periphery of the negative electrode active material layer 13, in addition to the activated carbon layer 23 disposed on the outer periphery end of the positive electrode active material layer 15 shown in FIG.

[0026] The main components of the lithium secondary battery according to this embodiment will be described below.

[0027] [Current collector] The current collector has a function of mediating the movement of electrons from the electrode active material layer. There are no particular limitations on the material constituting the current collector. For example, metals and conductive resins can be used as the material constituting the current collector.

[0028] The current collector may have a single layer structure made of a single material, or may have a laminate structure in which layers made of these materials are appropriately combined. From the viewpoint of reducing the weight of the current collector, it is preferable to include at least a conductive resin layer made of a resin having conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector. Furthermore, if the negative electrode active material layer and the positive electrode active material layer described later are conductive by themselves and can perform a current collecting function, it is not necessary to use a current collector as a member separate from these electrode active material layers. In such a form, the negative electrode active material layer described later constitutes the negative electrode as it is, and the positive electrode active material layer described later constitutes the positive electrode as it is.

[0029] [Negative electrode (negative electrode active material layer)] In the secondary battery according to this embodiment, the negative electrode active material layer 13 includes a negative electrode active material containing lithium. Such a negative electrode active material absorbs lithium ions desorbed from the positive electrode during charging, and releases lithium ions during discharging. The type of the negative electrode active material containing lithium is not particularly limited, and may include metallic lithium and lithium-containing alloys. Examples of the lithium-containing alloy include alloys of Li and at least one of Au, Ag, In, Al, Si, and Sn. In some cases, two or more types of negative electrode active materials may be used in combination.

[0030] The content of the negative electrode active material in the negative electrode active material layer is not particularly limited, but is preferably within the range of 40 to 99 mass %, and more preferably within the range of 50 to 90 mass %, for example.

[0031] The negative electrode active material layer preferably further includes a solid electrolyte. By including the solid electrolyte in the negative electrode active material layer, the ionic conductivity of the negative electrode active material layer can be improved. Examples of the solid electrolyte include sulfide solid electrolytes and oxide solid electrolytes, and the sulfide solid electrolyte is preferable.

[0032] Examples of sulfide solid electrolytes include LiI-Li2S-SiS2, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, LiI-Li3PS4, LiI-LiBr-Li3PS4, Li3PS4, Li2S-P2S5-LiI, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n (where m and n are positive numbers, and Z is Ge, Zn, or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (wherein x and y are positive numbers, and M is any one of P, Si, Ge, B, Al, Ga, and In). The description "Li2S-P2S5" means a sulfide solid electrolyte obtained by using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions.

[0033] The sulfide solid electrolyte may have, for example, a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of sulfide solid electrolytes having a Li3PS4 skeleton include LiI-Li3PS4, LiI-LiBr-Li3PS4, and Li3PS4. Examples of sulfide solid electrolytes having a Li4P2S7 skeleton include Li-PS solid electrolytes called LPS (for example, Li7P3S 11 ) As the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P xAn LGPS or the like represented by S4 (where 0 < x < 1) may be used. Among them, the sulfide solid electrolyte contained in the active material layer is preferably a sulfide solid electrolyte containing P element, and more preferably, the sulfide solid electrolyte is a material mainly composed of Li2S-P2S5. Furthermore, the sulfide solid electrolyte may contain a halogen (F, Cl, Br, I). In a preferred embodiment, the sulfide solid electrolyte contains Li6PS5X (where X is Cl, Br or I, preferably Cl).

[0034] Also, when the sulfide solid electrolyte is of the Li2S-P2S5 system, the ratio of Li2S and P2S5 is preferably in the range of Li2S:P2S5 = 50:50 to 100:0 in terms of molar ratio, and more preferably Li2S:P2S5 = 70:30 to 80:20.

[0035] Also, the sulfide solid electrolyte may be a sulfide glass, a crystallized sulfide glass, or a crystalline material obtained by a solid-phase method. The sulfide glass can be obtained, for example, by performing mechanical milling (such as a ball mill) on a raw material composition. Also, the crystallized sulfide glass can be obtained, for example, by performing heat treatment on the sulfide glass at a temperature equal to or higher than the crystallization temperature. Also, the ionic conductivity (for example, Li ion conductivity) of the sulfide solid electrolyte at room temperature (25 °C) is, for example, 1×10 -5 S / cm or more, preferably 1×10 -4 S / cm or more. The value of the ionic conductivity of the solid electrolyte can be measured by an alternating current impedance method.

[0036] Examples of the oxide solid electrolyte include compounds having a NASICON-type structure. As an example of a compound having a NASICON-type structure, a compound represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0 ≦ x ≦ 2) (LAGP), a compound represented by the general formula Li 1+x Al x Ti 2-x(PO4)3 (0≦x≦2) (LATP) and the like. Another example of an oxide solid electrolyte is LiLaTiO (for example, Li 0.34 La 0.51 TiO3), LiPON (e.g., Li 2.9 PO 3.3 N 0.46 ), LiLaZrO (e.g., Li7La3Zr2O 12 ) etc.

[0037] The shape of the solid electrolyte may be, for example, a particulate shape such as a spherical shape or an oval spherical shape, or a thin film shape. When the solid electrolyte is particulate, its average particle diameter (D 50 ) is not particularly limited, but is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. 50 ) is preferably 0.01 μm or more, and more preferably 0.1 μm or more.

[0038] The content of the solid electrolyte in the negative electrode active material layer is, for example, preferably in the range of 1 to 60 mass %, and more preferably in the range of 10 to 50 mass %.

[0039] The negative electrode active material layer may further contain at least one of a conductive assistant and a binder, in addition to the above-mentioned negative electrode active material and solid electrolyte.

[0040] The thickness of the negative electrode active material layer differs depending on the intended configuration of the secondary battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0041] [Solid electrolyte layer] In the secondary battery according to this embodiment, the solid electrolyte layer is interposed between the above-mentioned positive electrode active material layer and negative electrode active material layer, and is a layer that essentially contains a solid electrolyte.

[0042] There is no particular restriction on the specific form of the solid electrolyte contained in the solid electrolyte layer, and the solid electrolytes exemplified in the section on the negative electrode active material layer and their preferred forms can be similarly adopted. In some cases, a solid electrolyte other than the above-mentioned solid electrolyte may be used in combination. However, the content ratio of the sulfide solid electrolyte in the total amount of the solid electrolyte (100 mass%) is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, even more preferably 90 mass% or more, particularly preferably 95 mass% or more, and most preferably 100 mass%.

[0043] The solid electrolyte layer may further contain a binder in addition to the above-mentioned solid electrolyte.

[0044] The thickness of the solid electrolyte layer varies depending on the configuration of the intended lithium ion secondary battery, but from the viewpoint of improving the volumetric energy density of the battery, it is preferably 600 μm or less, more preferably 500 μm or less, and even more preferably 400 μm or less. On the other hand, there is no particular restriction on the lower limit of the thickness of the solid electrolyte layer, but it is preferably 10 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more.

[0045] [Cathode active material layer] In the secondary battery according to this embodiment, the positive electrode active material layer includes a positive electrode active material containing sulfur. The type of the positive electrode active material containing sulfur is not particularly limited, but may include, in addition to elemental sulfur (S), particles or thin films of organic sulfur compounds or inorganic sulfur compounds, and may be any material capable of releasing lithium ions during charging and absorbing lithium ions during discharging by utilizing the oxidation-reduction reaction of sulfur. Examples of the organic sulfur compound include disulfide compounds, sulfur-modified polyacrylonitrile, sulfur-modified polyisoprene, rubeanic acid (dithiooxamide), polycarbonate sulfide, and the like, which are typified by compounds described in the pamphlet of International Publication No. 2010 / 044437. Among these, disulfide compounds, sulfur-modified polyacrylonitrile, and rubeanic acid are preferred, and sulfur-modified polyacrylonitrile is particularly preferred. As the disulfide compound, a compound having a dithiobiurea derivative, a thiourea group, a thioisocyanate, or a thioamide group is more preferred. Here, the sulfur-modified polyacrylonitrile is a modified polyacrylonitrile containing sulfur atoms, which is obtained by mixing sulfur powder with polyacrylonitrile and heating the mixture under an inert gas or under reduced pressure. Its estimated structure is, for example, as shown in Chem. Mater. 2011, 23, 5024-5028, in which polyacrylonitrile is ring-closed to form a polycyclic ring, and at least a part of S is bonded to C. The compound described in this document has a peak at 1330 cm in the Raman spectrum. -1 and 1560cm -1 There is a strong peak signal near 307 cm -1 , 379cm -1 , 472cm -1 , 929cm -1There is a peak around 1000 nm. On the other hand, inorganic sulfur compounds are preferred because of their excellent stability, and specific examples thereof include sulfur element (S), Li2S, TiS2, TiS3, TiS4, NiS, NiS2, CuS, FeS2, MoS2, and MoS3. Among them, S, Li2S, S-carbon composite, TiS2, TiS3, TiS4, FeS2, and MoS2 are preferred, sulfur element (S), Li2S, TiS2, and FeS2 are more preferred, and sulfur element (S) or Li2S is particularly preferred from the viewpoint of high capacity. As the sulfur element (S), α-sulfur, β-sulfur, or γ-sulfur having an S8 structure can be used. These sulfur elements (S) absorb lithium ions during discharge and exist in the positive electrode active material layer in the form of lithium (poly)sulfides.

[0046] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, other positive electrode active materials than those mentioned above may be used. However, the content ratio of the positive electrode active material containing sulfur in the total amount of the positive electrode active material (100% by mass) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, particularly preferably 95% by mass or more, and most preferably 100% by mass.

[0047] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is preferably within the range of 35 to 99 mass %, and more preferably within the range of 40 to 90 mass %, for example.

[0048] The positive electrode active material layer also preferably contains a solid electrolyte, and more preferably contains a sulfide solid electrolyte. The specific form and preferred form of the solid electrolyte such as the sulfide solid electrolyte may be the same as those described in the above-mentioned negative electrode active material layer. Furthermore, the positive electrode active material layer may further contain a conductive assistant and / or a binder.

[0049] [Adsorbent] There is no particular restriction on the specific configuration of the adsorbent, and it is sufficient that the adsorbent can adsorb the sulfur-containing positive electrode active material that melts or sublimes when the battery is exposed to high temperatures. Examples of such adsorbents include porous materials such as carbon materials or oxide materials. Examples of carbon materials as porous materials include activated carbon and mesoporous carbon. Examples of oxide materials as porous materials include silica, alumina, zirconia, ceria, titania, and zeolite. All of these materials have excellent heat resistance and a large pore volume relative to their own bulk volume, so they are excellent in the ability to adsorb the sulfur-containing positive electrode active material under high temperature conditions. There is no particular restriction on the pore diameter of the pores of the porous material, but from the viewpoint of effectively adsorbing the sulfur-containing positive electrode active material, the pore diameter is preferably 1 to 500 nm. For the same reason, it is preferable that the porous material has a hydroxy group, a carboxy group, an aldehyde group, or an ester group on its surface.

[0050] There is no particular restriction on the specific value of the volume of the pores of the porous material arranged in the power generating element. However, the total volume of the pores of the porous material arranged in the power generating element is preferably 50% or more, more preferably 60% or more, even more preferably 70% or more, even more preferably 80% or more, particularly preferably 90% or more, and most preferably 100% or more, based on the total volume of the positive electrode active material that can be melted or sublimated. According to these forms, the adsorbent can adsorb most of the sulfur-containing positive electrode active material that is melted or sublimated under high temperature conditions, so that the effect of the present invention can be effectively exhibited.

[0051] [Protection Department] There is no particular restriction on the specific configuration of the protective part, and it may be made of a material that does not contain an adsorbent and can physically block the movement of the sulfur-containing positive electrode active material melted or sublimated under high temperature conditions to the negative electrode active material layer. Examples of such materials include heat-resistant insulating materials as described in Patent Document 1. Specific examples include aliphatic polyamides such as nylon 6 (melting point 222°C), nylon 46 (melting point 290°C), and nylon 66 (melting point 262°C), polyester resins such as polybutylene terephthalate (melting point 224°C), polyethylene terephthalate (melting point 256°C), and polycyclohexane dimethylene terephthalate (melting point 290°C), and super engineering plastics such as polyether ether ketone (melting point 334°C).

[0052] The protective part is preferably disposed at the outer peripheral end of at least one of the positive electrode active material layers and / or at least one of the negative electrode active material layers, and more preferably disposed so as to cover the outer periphery of the adsorbent when the protective part is disposed. By adopting such a configuration, the movement of the sulfur-containing positive electrode active material melted or sublimated under high temperature conditions to the negative electrode active material layer is physically blocked. This action, combined with the adsorption action of the adsorbent, makes it possible to prevent the progress of local battery reaction due to contact of the sulfur-containing positive electrode active material with the negative electrode active material layer and the resulting decrease in battery capacity.

[0053] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The positive electrode current collector plate 27 and the negative electrode current collector plate 25 may be made of the same material or different materials.

[0054] [Positive and negative leads] Although not shown in the figures, the current collectors (11", 11') and the current collecting plates (27, 25) may be electrically connected via positive and negative electrode leads. As the constituent materials of the positive and negative electrode leads, materials used in known lithium ion secondary batteries may be similarly used. Note that the parts removed from the exterior are preferably covered with a heat-resistant insulating heat-shrink tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing electric leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0055] [Battery exterior materials] As the battery exterior material, a known metal can case can be used, or a bag-shaped case using an aluminum-containing laminate film 29 capable of covering the power generating element as shown in Figs. 1 and 2 can be used.

[0056] Although one embodiment of the all-solid-state lithium secondary battery has been described above, the present invention is not limited to the configuration described in the above embodiment, and can be appropriately modified based on the recitations of the claims.

[0057] For example, in the all-solid-state lithium secondary battery according to the present embodiment, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular limit to the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and leakage of the liquid electrolyte (electrolytic solution) does not occur.

[0058] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.

[0059] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. Then, a large capacity, high output assembled battery (battery module, battery pack, etc.) suitable for a vehicle driving power source or an auxiliary power source that requires a high volumetric energy density and a high volumetric output density can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large capacity assembled battery can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.

[0060] [vehicle] The battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a battery with excellent long-term reliability and long life can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, if the battery or a battery pack formed by combining a plurality of batteries is used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles), the vehicle will have a long life and high reliability. However, the application is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for an uninterruptible power supply device or the like. EXAMPLES

[0061] The present invention will be described in more detail below with reference to examples. However, the technical scope of the present invention is not limited to the following examples. In the following, the tools and devices used in the glove box were thoroughly dried in advance.

[0062] <Example of all-solid-state lithium secondary battery production> <Comparative Example 1> First, sulfur element (S) as a positive electrode active material, acetylene black as a conductive additive, and sulfide solid electrolyte (LPS (Li2S-P2S5)) were weighed out to a mass ratio of 50:30:20, mixed in an agate mortar in a glove box, and then further mixed and stirred in a planetary ball mill. 2 parts by mass of styrene-butadiene rubber (SBR) were added to 100 parts by mass of the obtained mixed powder, and xylene was added as a solvent to prepare a positive electrode active material slurry. Next, the positive electrode active material slurry prepared above was applied to an aluminum foil as a positive electrode current collector, and dried to form a positive electrode active material layer, thereby producing a positive electrode.

[0063] On the other hand, LPS and SBR were mixed in a mass ratio of 95:5, and xylene was added as a solvent to prepare a solid electrolyte slurry. Next, the solid electrolyte slurry prepared above was applied to the exposed surface of the positive electrode active material layer of the positive electrode prepared above, and dried to prepare a positive electrode / solid electrolyte layer laminate. This positive electrode / solid electrolyte layer laminate was cut out so that the coating area of ​​the active material was 2.5 cm long x 2.0 cm wide. A negative electrode in which a Li foil (negative electrode active material layer) and a Ni foil (negative electrode current collector) of the same dimensions were overlapped was attached to the cut-out laminate so that the Li foil was located on the solid electrolyte layer side, and a predetermined pressure was applied to compress the negative electrode. Then, an Al tab lead and a Ni tab lead were welded to the Al foil and the Ni foil, respectively, to prepare a power generation element. The power generation element thus prepared was placed in an aluminum laminate film and sealed under reduced pressure to prepare a test cell.

[0064] <Comparative Example 2> LiNi was used instead of sulfur (S) as the positive electrode active material. 0.5 Mn 0.3 Co 0.2 A test cell of this comparative example was produced in the same manner as in Comparative Example 1 described above, except that powder of O2 (NMC composite oxide) was used.

[0065] <Comparative Example 3> The test cell of this comparative example was prepared in the same manner as in Comparative Example 1 described above, except that a resin layer (PET resin layer) made of polyethylene terephthalate (PET) was arranged in a frame shape around the outer periphery of the positive electrode active material layer constituting the power generating element.

[0066] <Example 1> First, activated carbon having a pore volume of 2 mL / g and acrylonitrile-butadiene rubber (NBR) were mixed in a mass ratio of 90:10, and xylene was added as a solvent to prepare an adsorbent slurry. The adsorbent slurry thus prepared was applied so as to cover the outer peripheral end of the positive electrode active material layer constituting the power generating element, and dried to arrange an activated carbon layer containing the adsorbent, activated carbon. Then, a PET resin layer similar to that of Comparative Example 3 described above was arranged on the outer periphery of the activated carbon layer. Except for these, the test cell of this example was prepared by the same method as that of Comparative Example 1 described above.

[0067] <Example 2> The test cell of this example was produced in the same manner as in Example 1 above, except that the PET resin layer was not disposed after disposing the activated carbon layer.

[0068] <Evaluation example of all-solid-state lithium secondary battery> Using an electrochemical diagnostic device (VSP-300, manufactured by BioLogic), in a constant temperature bath set at 90° C., the cycle characteristics of the all-solid-state lithium secondary battery prepared above were evaluated by the following method.

[0069] First, for batteries using sulfur as the positive electrode active material, the battery was placed in a thermostatic chamber, and after the cell temperature became constant, a current of 0.2 mA / cm was applied as cell conditioning. 2 The cell was discharged at a constant current density of 0.5 V to a cell voltage of 0.5 V, followed by a constant current / constant voltage charge to 2.5 V at the same current density (cut-off current 0.01 mA / cm 2)-constant current discharge (voltage 0.5 V) were performed for 10 cycles as a conditioning charge-discharge cycle. From the charge-discharge capacity value obtained after this conditioning charge-discharge cycle and the mass value of the sulfur active material contained in the positive electrode active material layer, the capacity value per mass of sulfur (mAh / g) was calculated.

[0070] The cycle characteristics were evaluated by fully charging the battery at 90°C under the condition of a 0.05C-2.5V constant current / constant voltage charge with a cutoff current of 0.01C, and then discharging at 0.05C with a cutoff voltage of 0.5V. The 10-cycle discharge capacity retention rate [%] was calculated as the percentage of the discharge capacity at the 10th cycle to the discharge capacity at the first cycle. The results are shown in Table 1 below.

[0071] On the other hand, for batteries using NMC composite oxide as the positive electrode active material, the battery was placed in a thermostatic chamber, and after the cell temperature became constant, a current of 0.2 mA / cm was applied as cell conditioning. 2 Constant current / constant voltage charging at a cell voltage of 4.2 V (cutoff current 0.01 mA / cm 2 ), followed by 10 conditioning charge-discharge cycles in which constant-current discharge at the same current density down to 3.0 V. The capacity per mass of the NMC composite oxide (mAh / g) was calculated from the charge-discharge capacity value obtained after this conditioning charge-discharge cycle and the mass value of the NMC composite oxide contained in the positive electrode active material layer.

[0072] The cycle characteristics were evaluated by fully charging the battery at 90°C under the conditions of a 0.05C-4.2V constant current / constant voltage charge with a cutoff current of 0.01C, and then discharging at 0.05C with a cutoff voltage of 3.0V. The 10-cycle discharge capacity retention rate [%] was calculated as the percentage of the discharge capacity at the 10th cycle to the discharge capacity at the first cycle. The results are shown in Table 1 below.

[0073] [Table 1]

[0074] From the results shown in Table 1, it can be seen that when an adsorbent capable of adsorbing sulfur is not arranged, when elemental sulfur is included as a positive electrode active material, the discharge capacity retention rate at 10 cycles is significantly reduced under high temperature conditions of 90 ° C. (Comparative Example 1). This is considered to be due to the fact that sulfur melts or sublimes due to exposure to high temperature, and comes into contact with the negative electrode active material layer (Li foil), and a local battery reaction progresses. In contrast, in Comparative Example 2, in which an NMC composite oxide that does not have the property of melting or sublimating is used as a positive electrode active material, a significant decrease in cycle characteristics as in Comparative Example 1 was not observed. In addition, sufficient improvement in cycle characteristics was not observed by merely arranging a frame-shaped protective part as described in Patent Document 1 at the outer peripheral end of the positive electrode active material layer (Comparative Example 3). In addition, in the evaluation of the cycle characteristics of Comparative Example 3, deformation of the cell caused by the expansion and deformation of the positive electrode active material layer was confirmed.

[0075] On the other hand, in Example 1 and Example 2 in which an activated carbon layer containing activated carbon, an adsorbent capable of adsorbing sulfur, was arranged at the outer peripheral end of the positive electrode active material layer, a remarkable improvement in cycle characteristics under high temperature conditions was confirmed. This is believed to be due to the fact that sulfur melted or sublimated under high temperature conditions was adsorbed by the adsorbent, and as a result, contact with the negative electrode active material layer and the progress of local battery reactions caused by this were suppressed. In addition, in Example 1 in which the above-mentioned frame-shaped protective part was further provided in addition to the arrangement of the adsorbent, a further improvement in cycle characteristics under high temperature conditions was observed. [Explanation of symbols]

[0076] 10a Stacked battery, 11' negative electrode current collector, 11” positive electrode current collector, 13 negative electrode active material layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21 Power generation elements, 23 activated carbon layer, 24 PET resin layers, 25 negative current collector plate, 27 Positive current collector, 29 Laminating film.

Claims

1. a positive electrode including a positive electrode active material layer containing a positive electrode active material including sulfur; a negative electrode including a negative electrode active material layer containing a negative electrode active material including lithium; a solid electrolyte layer interposed between the positive electrode active material layer and the negative electrode active material layer; A power generating element having the above structure is enclosed inside a battery exterior material, an adsorbent capable of adsorbing the positive electrode active material is disposed in an internal space of the battery exterior material in which the power generating element is enclosed; A lithium secondary battery in which the adsorbent is disposed on an outer peripheral end portion of at least one of the positive electrode active material layers and / or at least one of the negative electrode active material layers (excluding a lithium secondary battery in which the adsorbent covers the entire surface of the positive electrode active material layer other than a portion in contact with a positive electrode current collector).

2. The lithium secondary battery according to claim 1 , wherein the adsorbent is made of a porous material.

3. The lithium secondary battery according to claim 2 , wherein the porous material comprises a carbon material or an oxide material.

4. The lithium secondary battery according to claim 3 , wherein the porous material is activated carbon, mesoporous carbon, silica, alumina, zirconia, ceria, titania or zeolite.

5. 5. The lithium secondary battery according to claim 2, wherein the porous material has a hydroxy group, a carboxy group, an aldehyde group or an ester group on the surface thereof.

6. The lithium secondary battery according to any one of claims 1 to 5, wherein the adsorbent is disposed on a surface of an active material layer in a portion not facing a counter electrode at an outer peripheral end of at least one of the positive electrode active material layer and / or at least one of the negative electrode active material layer.

7. The lithium secondary battery according to any one of claims 1 to 6, wherein the adsorbent is disposed on a surface of the solid electrolyte layer at an outer peripheral end of at least one of the positive electrode active material layer and / or at least one of the negative electrode active material layer.

8. The lithium secondary battery according to any one of claims 1 to 7, wherein a protective part not containing the adsorbent is further disposed on an outer peripheral end portion of at least one of the positive electrode active material layers and / or at least one of the negative electrode active material layers.

9. The lithium secondary battery according to claim 8 , wherein the protective portion is disposed so as to cover an outer periphery of the adsorbent.

10. The lithium secondary battery according to claim 1, wherein the positive electrode active material layer and the solid electrolyte layer are in direct contact with each other.

Citation Information

Patent Citations

  • Lithium sulfur battery provided with adsorption layer

    CN102185158A

  • Electroactive sulfur material and secondary battery using the same

    JP2001527276A

  • Mesoporous carbon composite material and secondary battery using the same

    JP2010095390A

  • All-solid-state battery

    JP2011124084A

  • Method of manufacturing electrode body, and electrode body

    JP2012038425A